Evaluation of advanced curve speed warning system for fire trucks. (November 2021) - Simeonov, Peter; Hsiao, Hongwei; Nimbarte, Ashish; Current, Richard; Ammons, Douglas; Choi, Hee-Sun; Rahman, Md Mahmudur; Weaver, Darlene
Abstract: A curve speed warning system (CSWS) for firetrucks was developed and tested in this study. The CSWS algorithm was developed based on guidelines in the public domain for general vehicles and modified for firetrucks for their configuration and emergency driving. Twenty-four firefighters participated in the test in a driving simulator. The results show that the CSWS was effective in issuing preemptive warnings when the drivers were approaching curves with unsafe speed during emergency responses. Drivers reduced their driving speed at curve approaching and entering phases for most challenging curves, without affecting the overall time in completing the test route. Drivers had reduced number of severe braking and decreased average in-curve distance traveled over the safety speed limits, when the CSWS was in use. Drivers also rated the CSWS as assisting, effective and useful. In summary, the CSWS can enhance firetruck safety during emergency driving without sacrificing drivers' precious response time. Highlights: A curve speed warning system for firetrucks was evaluated in a driving simulator. The warning system reduced the driving speed at curve approach and curve entry. The warning system reduced the number of severe braking events. The warning system reduced the in-curve distance traveled over the safety speed. The warning system was well accepted and rated as assisting, effective, and useful.